A meditação como área de conhecimento: estudo cientométrico - Jane Rodrigues Guirado (2020)
This study aims to analyze the insertion of the theme Meditation in the core of scientific journals in the medical field to identify the most productive countries in research results and their communication in medical scientific journals from 2009 to 2018, indexed in the Web of Science and SCOPUS databases. The motivation for selecting the meditation theme was because this theme has grown and has been presented as one of the most widely used Complementary Therapies worldwide. The choice of the cited bases was due to its multidisciplinary coverage and to index high impact journals.The time frame of 10 was adopted because it makes possible to assess the evolution of this theme in recent years. The theoretical foundation covers authors and concepts of scientific communication, metric studies and the field of Complementary Therapies. This is a descriptive, Scientometric study with a quantitative approach. Data analysis and systematization tools were: Web of Science – Main Collection and SCOPUS (databases), Journal Citation Reports and SCImago Journal & Country Rank; Periodical Portal CAPES, Excel program and Wordsift tool. The follow categories were analyzed: Scientific production by country; Nucleus of journals from the five countries; Co-authorship network; Theme representativeness / Keywords; and Scientific production X Citation.In the Scientific production by country, the ranking of leading countries in the research related to the topic under study was identified: in the Web of Science database (1st position: United States; 2nd position: England; 3rd position: Australia; 4th position: Canada; and 5th position: India); in the SCOPUS base (1st position: United States; 2nd position: United Kingdom; 3rd position: India; 4th position: Australia; and 5th position: Canada). In the Core category of journals, it was identified that most of the journals' titles are of high impact and come from countries in North America and Europe, in both bases. It was also identified that the journals are classified in several categories in the medical field.In the Representativeness of the theme / Keywords it was noticed that the keywords cited in the articles by the author and by the databases refer to the most varied medical specialties. With regard to Co-authorship, the United States was the country that stood out as the largest partner of the four countries in the two databases, except with Australia (SCOPUS). Most of these partnerships took place between universities in the five countries, in both databases. In most studies, multiple authorship occurred in the five countries. Scientific Production X Citation showed that the Elite of producers from the five countries under study, on both bases, is formed by a small group of researchers. This group corresponds to one or at most two authors who published between 26 and 70 articles on the topic. The Front of research showed that the big producers have published their studies, mostly in English and in journals indexed in the two bases. It is understood that this study may contribute to the knowledge of important dimensions of the studies carried out by five leading countries on this subject.